Hear our voices: A Photovoice project with children who are orphaned and living with HIV in a Ugandan group home - Fournier, Bonnie; Bridge, Andrea; Kennedy, Andrea Pritchard; Alibhai, Arif; Konde-Lule, Joseph (Children and Youth Services Review, 2014)
In June 2010, we conducted a qualitative participatory research study to explore the experience of orphaned, HIV seropositive children who live in a group home in semi-urban western Uganda. Photovoice was used as a participatory method to enhance storytelling with children between 12 and 18years (n=5 girls; n=8 boys). In previous project work done by the research team in Uganda, children's affirming experiences in their group home suggested an extension to the dominant view that favors extended family placements, and raises the need for further inquiry regarding institutional care. Children in this study revealed how the group home supported key protective factors in their everyday lives that promote well-being, and resilience for coping with challenges such as stigma. Children expressed how their group home fostered a sense of belonging and appreciation for nature, home, resources and community. Children also described their hardships stemming from stigma, including associated psychological, emotional and social challenges. This forces us to re-think the role of institutional care for orphaned children who are HIV seropositive, guided by the unique perspective of children themselves. This research extends our understanding of key protective factors, while also challenging the dominant view to include institutional care as an effective placement option for those that require specialized care and support. Moreover, findings demonstrate that HIV seropositive orphaned children who live in a group home setting experience protective factors supporting their psychological, emotional and social well-being.
Keywords: Institutional care; HIV Stigma; Photovoice; Orphaned children